SPONTAN İNTRAKRANYAL HİPOTANSİYON: OLGU SUNUMU - ÖZTÜRK MUNGAN, Semra; ALBAYRAM, Sait; SAİP, Sebahattin (Cerrahpaşa Medical Journal, 2014)
Background.- Spontaneous intracranial hypotension is a rarely seen benign disease with unknown etiology. The cardinal symptom is postural headache which occurred without any reason. One or more of the symptoms such as pain or stiffness of the neck, interscapular pain, nausea, vomiting, vertigo, horizontal diplopia, changed in hearing, visual blurring, face numbness and weakness in upper extremities can accompany. Observation.- By the way of the case in which we have diagnosed spontaneous intracranial hypotension with the signs of postural headache, low cerebrospinal fluid pressure and diffuse pachymeningeal contrast enhancement we aimed to bring on date the problems in diagnosis and treatment of this rarely seen antity.